Pengaruh Penerapan Segmenting, Targeting, dan Positioning dalam Meningkatkan Penjualan di Mutia Kaos Banjaran - Sari Wiyanti; Siti Nurhidayati; Salsabila Syafa A; Naela Azkiyah Salsabila (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The effect of Segmenting, Targeting, and Positioning (STP) tactics on Mutia Kaos Banjaran's sales performance is investigated in this study. Finding the impact of each STP component, both separately and collectively, on sales is the goal. The study employs a quantitative methodology, gathering information from 100 respondents via questionnaires. While positioning has no discernible effect on sales, the results show that segmenting and targeting significantly increase sales. Targeting students and private employees, as well as segmenting the market to focus on young female consumers between the ages of 21 and 30, proved to be successful tactics. However, to improve consumer perception and brand identity, positioning needs to be improved. All things considered, STP tactics greatly increase sales; they account for 76.9% of the variation in sales. These results highlight how crucial targeted and integrated marketing strategies are to improving company performance.